Synthesis and characterization of polythiophenes from hydrazone derivatives sidegroups - Trung, Vu Quoc; Linh, Nguyen Ngoc; Linh, Duong Khanh; Pfleger, Jiri (Vietnam Journal of Chemistry, 2016)
Polythiophenes with various substituted hydrazone side groups were synthesized using a chemical oxidative coupling reaction. Analyses of IR and NMR spectra confirmed the expected structure of new synthesized polymers and confirmed suitability of the suggested synthetic route. Surface properties, morphology and thermal stability of the prepared polymers were studied by SEM and TGA methods. Two derivatives were found to have a good solubility in several water-miscible solvents. They can be used as active materials in electrochromic and electronic devices.